Development of highly recombinant inbred populations for quantitative-trait locus mapping - Boddhireddy, Prashanth (Kansas State University, 2009)
The goal of quantitative-trait locus (QTL) mapping is to understand the genetic architecture of an organism by identifying the genes underlying quantitative traits. It targets gene numbers and locations, interaction with other genes and environments, and the sizes of gene effects on the traits. QTL mapping in plants is often done on a population of progeny derived from one or more designed, or controlled, crosses. These crosses are designed to exploit correlation among marker genotypes for the purposes of mapping QTL. Reducing correlations between markers can improve the precision of location and effect estimates by reducing multicollinearity. The purpose of this thesis is to propose an approach for developing experimental populations to reduce correlation by increasing recombination between markers in QTL mapping populations especially in selfing species. QTL mapping resolution of recombinant inbred lines (RILs) is limited by the amount of recombination RILs experience during development. Intercrossing during line development can be used to counter this disadvantage, but requires additional generations and is difficult in self-pollinated species. In this thesis I propose a way of improving mapping resolution through recombination enrichment. This method is based on genotyping at each generation and advancing lines selected for high recombination and/or low heterozygosity. These lines developed are called SA-RILs (selectively advanced recombinant inbred lines). In simulations, the method yields lines that represent up to twice as many recombination events as RILs developed conventionally by selfing without selection, or the same amount but in three generations, without reduction in homozygosity. Compared to methods that require maintaining a large population for several generations and selecting lines only from the finished population, the method proposed here achieves up to 25% more recombination. Although SA-RILs accumulate more recombination than conventional RILs and can be used as fine-mapping populations for selfing species, the effectiveness of the SA-RIL approach decreases with genome size and is most valuable only when applied either to small genomes or to defined regions of large genomes. Here I propose the development of QTL-focused SA-RILs (QSA-RILs), which are SA-RILs enriched for recombination in regions of a large genome selected for evidence for the presence of a QTL. This evidence can be derived from QTL analysis in a subset of the population at the F2 generation and/or from previous studies. In simulations QSA-RILs afford up to threefold increase in recombination and twofold increase in accuracy of QTL position estimate in comparison with RILs. The regional-selection method also shows potential for resolving QTL linked in repulsion. One of the recent Bayesian methods for QTL mapping, the shrinkage Bayesian method (BayesA (Xu)), has been successfully used for estimating marker effects in the QTL mapping populations. Although the implementation of the BayesA (Xu) method for estimating main effects was described by the author, the equations for the posterior mean and variance, used in estimation of the effects, were not elaborated. Here I derive the equations used for the estimation of main effects for doubled-haploid and F2 populations. I then extend these equations to estimate interaction effects in doubled-haploid populations. These derivations are helpful for an understanding of the intermediate steps leading to the equations described in the original paper introducing the shrinkage Bayesian method.
Keywords: Genetics; Statistical Genetics; Biostatistics; Agriculture, Agronomy (0285); Biology, Biostatistics (0308); Biology, Genetics (0369)